Effects of fish oil supplementation on bone turnover markers in depression: a pilot study - Wang, Feifei; Yuan, Hui; Jin, Kun; Tang, Hui; Guo, Jimin; Wang, Chuan-Yue; Chen, Jindong; Dong, Fang; Wang, Lu (Frontiers in Nutrition, 2024)
Background and objectiveThere is a close correlation between bone loss, depression, and antidepressants. N-3 PUFA supplementation has been considered an effective add-on therapeutic approach in ameliorating bone loss and relieving depression. However, the adjunctive effect of n-3 PUFA on bone metabolism in participants with depression is still unknown. This is a pilot study to investigate the dynamics of bone metabolism in depression and evaluate the efficacy of fish oil on bone loss in depression.MethodsIn this study, we focused on the change of bone turnover markers in depression, the effect of n-3 PUFA supplementation on bone turnover markers, and its association with clinical characteristics. A case–control study and a secondary analysis of a previously published randomized clinical trial (NCT03295708) that evaluates the efficacy of n-3 PUFA supplementation in venlafaxine-treated depressed participants have been included.ResultsThe levels of PINP (z = −2.233, p = 0.026) in depressed participants were significantly increased compared with healthy controls at baseline. The secondary analysis has shown significant differences exited on CTX (χ2 = 4.848, p = 0.028) and OSTEOC (χ2 = 6.178, p = 0.013) between n-3 PUFA and placebo group. The levels of CTX and OSTEOC (p < 0.05) significantly decreased in the placebo group, which indicates that venlafaxine treatment reduces both bone formation and resorption markers. While the levels of OSTEOC and PINP were increased in the n-3 PUFA group (p < 0.05). Moreover, the change in bone turnover markers showed consistency with clinical symptomatic outcomes.ConclusionParticipants with first-diagnosed, drug-naïve depression show active bone formation. Venlafaxine decreases bone remodeling, while n-3 PUFA increases bone formation, bringing light to preventing and treating bone loss in depression.Clinical trial registrationClinicalTrials.gov, NCT03295708.